ANTICONVULSANT AND SEDATIVE ACTIVITIES OF EXTRACTS OF CARISSA CARANDAS LEAVES. - Shinde, Manisha; Gilhotra, Ritu; Chaudhari, Sanjay (Journal of Drug Delivery and Therapeutics, 2018)
The present study was carried out to find out the preliminary phytochemical properties, anticonvulsant and sedative activities of the petroleum ether, ethyl acetate and ethanol extract of Carissa carandas leaves. The standard methods were used to screen the preliminary photochemicals present  in petroleum ether, ethyl acetate and ethanol extracts of Carissa carandas leaves. The anticonvulsant efficacy of the extracts was determined using pentylenetetrazole (PTZ) in experimental animal models using diazepam as standard drug and the sedative effect was evaluated using pentobarbitone that induced sleep in mice. The efficacy of the extracts was compared against the standard drug Diazepam .The preliminary phytochemical investigation shows presence of alkaloids, glycoside, tannins,terpins . The crude extracts of ethanolic, ethyl acetate and petroleum ether at a dose 400 mg/kg has been found to significantly reduce the extensor and stupor and offer protection against convulsion induced by PTZ. The petroleum ether, ethyl acetate and ethanolic extract found to be non significant at a dose of 100 mg/kg in flexion.It is seen that the crude extracts of ethanolic, ethyl acetate and petroleum ether Of Carissa carandas leaves significantly (p < 0.05) prolonged the time of sodium pentobarbital-induced hypnosis. However, the animal study revealed that the anticonvulsant and sedative activities of Carissa carandas can be used in the treatment of epilepsy.Key words- Carissa carandas, anticonvulsant, pentobarbitone, hypnosis, epilepsy.